TIMP2 rs2277698 polymorphism associated with adverse IVF outcomes in Han Chinese women - Lee, Chun-I.; Lee, Yu-Jen; Lee, Tsung-Hsien; Lee, Chi-Ying; Tsao, Hui-Mei; Cheng, En-Hui; Huang, Chun-Chia; Yang, Shun-Fa; Lee, Maw-Sheng (Frontiers in Endocrinology, 2025)
BackgroundMatrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) are critical regulators of extracellular matrix (ECM) proteolysis and play a pivotal role in trophoblast invasion during embryo implantation. This study aimed to investigate the effects of single-nucleotide polymorphisms (SNPs) in MMP and TIMP genes on clinical outcomes in women undergoing in vitro fertilization (IVF).MethodsThis retroprospective study included 1014 women undergoing their first fresh IVF cycle without donor eggs at Lee Women’s Hospital between January 2014 and December 2015. Peripheral blood samples were collected from all participants for DNA extraction and SNP genotyping using real-time polymerase chain reaction. The study focused on three SNPs: TIMP1 (rs4898 C/T), TIMP2 (rs2277698 C/T), and MMP2 (rs243865 C/T). Associations between these SNPs and IVF outcomes, including clinical pregnancy, embryo implantation, abortion, and live birth rates, were analyzed.ResultsAmong 560 patients analyzed, no significant differences were observed in baseline characteristics between the live birth and non-live birth groups. However, the minor alleles (CT+TT) of MMP2 (rs243865) and TIMP2 (rs2277698) were significantly more frequent in the non-live birth group (MMP2: 24.4% vs. 17.7%, p = 0.044; TIMP2: 48.1% vs. 34.4%, p = 0.001). In contrast, no significant differences in the genotype distribution of TIMP1 (rs4898) were noted between the groups. Logistic regression analysis identified the minor T allele of TIMP2 as a significant predictor of non-live birth (adjusted odds ratio: 1.725; 95% CI: 1.217–2.445; p = 0.002). Combined genotypes of MMP2/TIMP2, such as CC/CT+TT and CT+TT/CT+TT, were associated with an increased risk of non-live birth, even after adjusting for covariates.ConclusionsThe study demonstrates that the minor T allele of TIMP2 (rs2277698 C/T) is associated with poor IVF outcomes, particularly non-live birth. This finding highlights the potential role of genetic variations in TIMP2 in influencing clinical outcomes of IVF. Further research is warranted to elucidate the underlying mechanisms in larger and more diverse populations.